Microbial ecology overview during anaerobic codigestion of dairy wastewater and cattle manure and use in agriculture of obtained bio-fertilisers. (December 2015) - Toumi, Jihen; Miladi, Baligh; Farhat, Amel; Nouira, Said; Hamdi, Moktar; Gtari, Maher; Bouallagui, Hassib
Graphical abstract: Highlights: The anaerobic co-digestion of dairy wastewater and cattle manure. The associated microbial community's were described by DGGE. The volatile solids removal and biogas yield reached 88.6% and 0.87 L/g VS. Syntrophic associations were essential to keep low H2 pressure. The digestate showed beneficial effects on the plants growth and crops. Abstract: The anaerobic co-digestion of dairy wastewater (DW) and cattle manure (CM) was examined and associated with microbial community's structures using Denaturing Gradient Gel Electrophoresis (DGGE). The highest volatile solids (VS) reduction yield of 88.6% and biogas production of 0.87 L/g VS removed were obtained for the C/N ratio of 24.7 at hydraulic retention time (HRT) of 20 days. The bacterial DGGE profile showed significant abundance of Uncultured Bacteroidetes, Firmicutes and Synergistetes bacterium. The Syntrophomonas strains were discovered in dependent association to H2 -using bacteria such as Methanospirillum sp., Methanosphaera sp. and Methanobacterium formicicum . These syntrophic associations are essential in anaerobic digesters allow them to keep low hydrogen partial pressure. However, high concentrations of VFA produced from dairy wastes acidification allow the growth of Methanosarcina species. The application of the stabilised anaerobic effluent on the agriculture soil showed significant beneficial effects on the forage corn and tomato plants growth and crops.